Education on human rights, view to Colombian scene - Russi Quiroga, Alba Luz (Universidad Pedagógica y Tecnológica de Colombia, 2011)
Human rights is not a new issue is the need that has emerged from a society with tensions and conflicts that cause dissatisfaction, violence, resentment and therefore desires self help, in order that every human being account of their responsibility to think and act against the situation that presents itself, generating confidence in himself and compromise of estimation, equality, non-discrimination, equity. In this challenge, education plays an important role not only use must shelter program content to include human rights knowledge in transversely in the exercise of docencia permeen all areas of knowledge, also include training of teachers, changing attitudes and paradigms in the same, in the treatment within the school and educational institutions, in the context of needs, interests and social potential of teachers and students. It is then a face articles reflecting the state of education in human rights in our country.